Parametric optimization of navigational paths multimode stabilization system and determine the course - Сущенко, О.А. (Proceedings of National Aviation University (archive), 2009)
The mathematical description of navigational loops for the multimode stabilization and course system is represented. Features of the parametric optimization for the system to be studied are considered.v Simulation results of the synthesized system are represented. Advantages of the suggested approach for the optimal synthesis of the stochastic systems are shown.